2017
DOI: 10.1149/2.0311707jes
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of High Performance Intermediate Temperature Alumina Substrate Supported Micro-Tubular SOFCs

Abstract: The central challenge of solid oxide fuel cell (SOFC) technology lies in how to achieve sufficient robustness and reliability while significantly reducing system and operating cost. This paper studied a novel alumina substrate supported micro-tubular SOFC with high performance at intermediate temperatures. An in-house built extrusion system in combination with modified phase-inversion method was used to fabricate micro-tubular alumina substrate with radially well-aligned micro-channel array. The gas permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…It has been confirmed in our early work that NiAl 2 O 4 remains chemical stability in a reducing atmosphere of wet hydrogen under 800 °C but is decomposed into Ni and α-Al 2 O 3 above 900 °C . To further examine chemical stability of NiAl 2 O 4 substrate in methane at elevated temperatures, the sintered substrates were first reduced in humidified hydrogen at 600 °C for 5 h, followed by treatment in dry methane for 10 h at 800 and 900 °C, respectively.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It has been confirmed in our early work that NiAl 2 O 4 remains chemical stability in a reducing atmosphere of wet hydrogen under 800 °C but is decomposed into Ni and α-Al 2 O 3 above 900 °C . To further examine chemical stability of NiAl 2 O 4 substrate in methane at elevated temperatures, the sintered substrates were first reduced in humidified hydrogen at 600 °C for 5 h, followed by treatment in dry methane for 10 h at 800 and 900 °C, respectively.…”
Section: Resultssupporting
confidence: 93%
“…In this respect, direct hydrocarbon fueled SOFCs are highly desired, and oxygen ions from cathode side might be the only oxygen source that can be used to inhibit carbon deposition (e.g., oxidize surface carbons) without sacrificing SOFC performance. It is noteworthy that although TPB sites are uniformly distributed in a thick Ni-cermet anode electrode in anode-supported SOFCs, studies have shown that electrochemical reactions are mainly confined within a narrow range near anode/electrolyte interface or effective reaction zone. , In other words, oxygen ions from cathode side would be largely consumed by electrochemical oxidation of fuel species in this effective reaction zone. As long as oxygen ions are continuously supplied, carbon deposition could be completely inhibited in this region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the reactions (4) and ( 5), when 𝐶𝐻 concentration is relatively low while that of mobile 𝑂 near the TPB sites are relatively high, the full oxidation of 𝐶𝐻 would occur; in other extreme situations of high 𝐶𝐻 concentration and low concentration of mobile 𝑂 , the partial oxidation of 𝐶𝐻 could take place. We have experimentally demonstrated that the microtubular substrate with radially well-aligned microchannels facilitates facile gas diffusion and is able to obtain very high gas permeability [35,36]. Accordingly, sufficiently high 𝐶𝐻 concentration would be maintained in the anode functional layer.…”
Section: Single-cell Performancesmentioning
confidence: 99%
“…The as-prepared slurry was de-aired for 10 min and then loaded into an in-house build spinneret extrusion system to obtain green microtubular substrate. The extrusion system and related extrusion process were detailed elsewhere [35][36][37]. The green substrate was sintered at 1100 o C in the air for 3hrs to achieve sufficient mechanical strength for subsequent functional layer coatings of NiO, NiO-Zr0.1SDC, YSZ, SDC, and LSCF sequentially.…”
Section: Single Microtubular Cell Fabricationmentioning
confidence: 99%